Numerical characterization of landing gear aeroacoustics using advanced simulation and analysis techniques. (1st September 2017) - Redonnet, S.; Ben Khelil, S.; Bulté, J.; Cunha, G.
Abstract: With the objective of aircraft noise mitigation, we here address the numerical characterization of the aeroacoustics by a simplified nose landing gear (NLG), through the use of advanced simulation and signal processing techniques. To this end, the NLG noise physics is first simulated through an advanced hybrid approach, which relies on Computational Fluid Dynamics (CFD) and Computational AeroAcoustics (CAA) calculations. Compared to more traditional hybrid methods (e.g. those relying on the use of an Acoustic Analogy), and although it is used here with some approximations made (e.g. design of the CFD-CAA interface), the present approach does not rely on restrictive assumptions (e.g. equivalent noise source, homogeneous propagation medium), which allows to incorporate more realism into the prediction. In a second step, the outputs coming from such CFD-CAA hybrid calculations are processed through both traditional and advanced post-processing techniques, thus offering to further investigate the NLG's noise source mechanisms. Among other things, this work highlights how advanced computational methodologies are now mature enough to not only simulate realistic problems of airframe noise emission, but also to investigate their underlying physics. Graphical abstract: Highlights: A landing gear noise problem is addressed using advanced computational and analysis techniques. The noise generation and propagation dynamics of the landing gear are investigated. Validity of the techniques employed and viability of the overall strategy is demonstrated. A step further towards the mitigation of aircraft noise problems via numerical simulation is made.